Front Cover: 1H NMR Chemosensing of Potassium Ions Enabled by Guest‐Induced Selectivity Switch of a Gold Nanoparticle/Crown Ether Nanoreceptor (ChemPlusChem 10/2019). Issue 10 (13th August 2019) - Sun, Xiaohuan; Rosa‐Gastaldo, Daniele; De Biasi, Federico; Rastrelli, Federico; Mancin, Fabrizio
Abstract : The cover picture shows an 18‐crown‐6‐functionalized gold nanoparticle interacting with potassium ions, tyramine, and phloretate ions. These are the components of a sensing system for detecting potassium ions in water by magnetization transfer 1 H NMR spectroscopy. Binding of potassium ions to the crown ether moieties switches the nanoreceptor preference from organic cations to organic anions. A ratiometric NMR signal is thus produced with a detection limit of 0.6 mM. Other ions, organic molecules, and even proteins present in the sample produce little interference. The modularity of this sensing approach can easily adapted to different analytes. Details are given in the Communication by F. Mancin and co‐workers on page 1498 in Issue 10, 2019 (DOI: 10.1002/cplu.201900028 ).